Hexahelix collaboration in developing halal tourism in Indonesia - Yudithia Yudithia; Ilham Sentosa; Eiad Yafi (Indonesian Tourism Journal, 2024)
Tourism collaboration is to create a series of tourism programs or activities that are more diverse, attractive, and sustainable to attract tourists to visit an area or tourist destination on an ongoing basis. The purpose of the Hexahelix collaborative research in the development of halal tourism in Indonesia is to examine the potential for halal tourism in Indonesia and how this potential can be optimally and sustainably developed through collaboration between Government, community, academia, private sector, law and the mass media which have their respective roles. The method of using post-positivism qualitative research sees reality as a construction continuously developed through subjective experiences, so post-positivism qualitative research emphasizes in-depth interpretation and understanding related to phenomena. Logical analysis can identify errors or weaknesses in an argument or ensure that the conclusions drawn from the argument are correct and consistent. The results show that the hexahelix collaboration significantly contributes to accelerating halal tourism development in Indonesia. In this study, it was also found that the development of halal tourism in Indonesia has enormous potential as a type of tourism trending and experiencing rapid growth in Indonesia and the world. Thus, it is hoped that the development of halal tourism in Indonesia can be successful and provide greater benefits for economic development and people's welfare.